Innovative Applications for Presenting Heritage in the Visual Arts Medium: A Case Study of the Omani Legends and Stories Exhibition - العجمى، ندى (جامعة السلطان قابوس - كلية الآداب والعلوم الاجتماعية, 2016)
إن معرض الأساطير والحكايات العمانية يعتبر نموذجا حيا لتوفير الفرص للفنانين العمانيين وعددهم 42 فنانا، لكي يبدعوا في تقديم التراث ضمن نصوص فنية بصرية لها تأثير مباشر في التطوير المجتمعي. للوصول إلى النتائج التي تبحث عن دور المرأة في الموروث الثقافي العماني، اعتمدت هذه الدراسة على مقابله سبعه من الفنانين العمانيين اللذين اختاروا قصصا شعبية مرتبطة بقضية المرأة وتحليل تلك القصص والأعمال الفنية ضمن إطار آخر المستجدات في الأبحاث العلمية في مجال القصص والأساطير الشعبية. أكد الفنانون العمانيون التشكيليون مدى مرونة هذا الموروث الشعبي الذي مازال قيمة متداولة في المجتمع العماني لدعم المرأة على مر الأجيال. وقد عكس الفنانون رؤيتهم المعاصرة لهذا الموروث الثقافي من خلال لوحاتهم الفنية وسلطوا الضوء على علاج القضايا التي تجب مناقشتها في المجتمع لكي تساهم في إزالة أية عوائق قد تحد من تعزيز وتطوير دور المرأة العمانية في المجتمع
In transforming the folk tale into a visual medium, contemporary artists have illuminated the remarkable flexibility of this cultural heritage. The Omani Legends and Stories exhibition held in 2012 featured forty-two contemporary artists inspired to re-interpret folk tales that encapsulated beliefs and values relevant in present-day Oman. Several years later, qualitative interviews were conducted with seven of the artists whose work depicted stories focused on representations of women. Together with some analysis of academic writing in the field of traditional tales, this study also garnered artists’ viewpoints as expressed in their art works and revealed in discussions with the artists themselves. It was found that there is continuity in the cultural values and beliefs across generations, that folk tales are still being passed on and that women were represented in them in an intriguingly positive light. The continuing observance of cultural restrictions practiced on women was not supported in either the folk tales or the artists’ own viewpoints. The example provided by Oman’s visual arts industry may inspire similar initiatives in other societies and further research on possible linkages between different art mediums that could be harnessed to further the betterment of women’s socio-cultural situation.
Keywords: الأدب الشعبى -- القصص الشعبية -- التراث الشعبى -- الأنشطة الثقافية -- الأساطير والخرافات -- المجتمع العمانى